Bai Bithaman Ajil (BBA) and Musharakah Mutanaqisah (MM): comparative analysis / Siti Norbaya Mohd Rashid ...[et al.] - Mohd Rashid, Siti Norbaya; Abd Rahman, Muhammad Abd Hadi; Che Yahya, Norliza Che; Md Rasid, Nor Farah (Faculty of Business and Management UiTM Shah Alam, 2020)
Malaysia has always be at the forefront of Shariah-compliant financial products and is seeing a growth in Shariah or Islamic home financing. This paper investigates the most important factors need to be considered by home buyers in choosing Islamic Home Financing. Specifically, this paper examines home buyers preference in choosing Islamic home financing beween Bai Bithaman Ajil (BBA) and Musharakah Mutanaqisah (MM). Ignorance on Maqasid al Shariah in Islamic home financing led to misinterpretation, disruption, chaos, and trivial conflicts among the contracting parties. busines stransactions, particularly for Islamic There are three main variables that are being used to identify most influenced factor which are Shariah compliant, pricing, and equality. Data was collected via questionnaires from 100 homebuyers who are taking either BBA or MM's home financing in Kota Bharu, Kelantan. Data was analysed using SPSS to analyse on Cronbach's alpha, frequency analysis, mean analysis, independent samples T-test and ANOVA. All variables have a significant value towards preference on Islamic home financing, it meet the purpose of the Shariah (Maqasid al Shariah). MM home financing mode is more preferable based on Mean value as Shariah compliant and Equality shows a higher value compared to BBA. Findings are useful as it may help Islamic bank managers to enhance their planning for Isamic home financing products and develop effective strategies accordingly that benefit their customers.